049 Real world evidence (RWE) on impact of age on long-term persistence to disease modifying therapies (DMTS) in relapsing-remitting multiple sclerosis (RRMS) in australia. (29th July 2019) - Kornberg, Andrew; Spelman, Tim; Schulz, Mark; Arora, Birendra; Chung, Eric; Juneja, Prabjot; Walker, Robert; Walt, Anneke van der; Butzkueven, Helmut
Abstract : Background: Age has been independently associated with higher rates of treatment discontinuation in multiple sclerosis. Objective: The current study examines the impact of age on persistence for all reimbursed DMTs for RRMS in Australia. Methods: The Pharmaceutical Benefits Scheme (PBS) 10% sample supplied by the Department of Human Services was used in this study. Eligible patients must have received a script for a reimbursed DMT for RRMS between September 2011 and February 2016. Patients were classified into five age-groups (ages 18–30; 31–40; 41–50; 51–60; 61+) and defined as persistent if their DMT script was filled within 4 months. Persistence was derived using the Kaplan-Meier method and hazard ratios (HR) to represent the relative rate of drop-off of different age groups. Results: Patients aged 18–30 (n=250) had a 44% increased risk of discontinuation (HR 1.44 (95%CI: 1.22–1.72) compared to the 'all ages' cohort (n=1, 866); no significant difference was observed for any other age group (HRs between 1.08 and 0.92). Patients in this 18–30 age-group had a significantly higher risk of discontinuation on injectable therapy (glatiramer acetate, interferon beta-1a, interferon beta-1b) compared to those on non-injectable therapy (dimethyl fumarate, fingolimod, natalizumab, teriflunomide) (HR 2.42 (95% CI: 1.63–3.61). Conclusions: Patients aged 18–30 were the least persistent age group in this study. Patients aged 18–30 were less persistent on injectable than non-injectable DMTs.